(untitled) (Revista de Ciências Agroveterinárias, 2013)
The burning of fields is a traditional tool for grassland management in Brazil. In the Northeast and Midwest regions, though much disputed in the scientific and by environmental organizations and society in general, it is a reality and common practice. In the South, specifically in the states of Santa Catarina and Rio Grande do Sul, this activity is widespread, which is mainly due to the steep topography and rock outcroppings, which makes grazing difficult to manage during the dry season (late winter). The possible reasons for the use of burning as a management tool could be related to the elimination of the plant material blasted by frost during the winter, which, according to farmers, would reduce spring growth. Other arguments raised by proponents of this practice are the degree of infestation of undesirable species in burned and unburned areas and the rate of regrowth of forage species after burning. The points cited are based mostly on visual observations with research carried out in areas that aren’t very representative, which often leads to erroneous conclusions or a misleading reality. Thus, this review aims to elucidate the main effects of burning on pasture, its advantages, disadvantages and particularly the damage caused by frequent and continuous use of burning as a management tool.